Munkapiaci áramlások, gereblyézés és a 2008 végén kibontakozó gazdasági válság foglalkoztatási hatásai - Zsombor Cseres-Gergely (Hungarian Academy of Sciences, Institute of Economics, 2010)
– Analyses of the Hungarian employment situation are almost always concerned only with the change in the number of the employed, unemployed and inactive, not paying particular attention to the flows between these states. This paper discusses a method of calculating labour market flows in a consistent way and the employment effects of the crisis unfolding after 2008. Separating supported and not-supported employment, I am attempting to show the employment effects of the "Pathway to work" programme. The method discussed proved to be feasible and useful in analysing the labour market. Results among others show that the apparent positive effect of the "Pathway to Work" programme on employment was not real, but mostly a statistical artefact in the period under consideration.
Keywords: J21; J63; C63; 330; labour market; flows; raking; Arbeitsmarkt; Arbeitsmobilität; Beschäftigungseffekt; Arbeitsmarktpolitik; Wirtschaftskrise; Ungarn